China in Pakistan and the wider region: A cautious but effective leader? - Basit, S; Torjesen, S; MacFarlane, SN (Taylor and Francis (Routledge), 2018)
This article assesses China–Pakistan-Afghanistan relations in the period 2014–2018 and asks whether China has exercised distinct pressure on Pakistan to be a more constructive partner for Afghanistan. A central argument is that even as China has failed to alter Pakistan’s policies significantly in the short term it is still continuing to successfully build power and trust in Pakistan and Afghanistan, as well as with their neighbours to the north and west. This bodes well for China’s exercise of regional leadership in a long-term perspective.